Unraveling the Contribution of Fluid Therapy to the Development of Augmented Renal Clearance in a Piglet Model - Dhondt, Laura; Croubels, Siska; De Paepe, Peter; Goethals, Klara; De Cock, Pieter; Devreese, Mathias (Frontiers in Pharmacology, 2021)
Augmented renal clearance (ARC) observed in the critically ill pediatric population has received an increased attention over the last years due to its major impact on the disposition and pharmacokinetics of mainly renally excreted drugs. Apart from an important inflammatory trigger, fluid administration has been suggested to contribute to the development of ARC. Therefore, the primary objective of this study was to evaluate the effect of continuous intravenous fluid administration on renal function using a conventional piglet animal model and to quantify the impact of fluid administration on the pharmacokinetics of renally excreted drugs. At baseline, twenty-four piglets (12 treatment/12 control; 7 weeks old, all ♂) received the marker drugs iohexol (64.7 mg/kg body weight (BW)) and para-aminohippuric acid (10 mg/kg BW) to quantify glomerular filtration rate and effective renal plasma flow, respectively. In addition, the hydrophilic antibiotic amikacin (7.5 mg/kg BW) was administered. Following this baseline measurement, the treatment group received fluid therapy as a constant rate infusion of 0.9% saline at 6 mL/kg/h over 36 hours. After 24 hours of fluid administration, the marker drugs and amikacin were administered again. When comparing both groups, a significant effect of fluid administration on the total body clearances of iohexol (p=0.032) and amikacin (p=0.0014) was observed. Clearances of iohexol and amikacin increased with on average 15 and 14%, although large interindividual variability was observed. This led to decreased systemic exposure to amikacin, which was manifested as decrease in area under the plasma concentration-time curve from time 0 h to infinity from 34,807 to 30,804 ng.h/mL. These results suggest that fluid therapy is a key factor involved in the development of ARC and should be taken into account when administering mainly renally excreted drugs. However, further research is necessary to confirm these results in children.